Bang e dara - Allama iqbal (Abdullah acadamey Lahore, 2009)
Bang-e-Dara by Allama Iqbal is a celebrated collection of poetry that reflects on themes of nationalism, spirituality, and the pursuit of self-awareness, inspiring generations with its profound messages.